An examination of the utilization of audit technology in influencing audit job performance / Nurul Fitri Mohd Noor ... [et al.] - Mohd Noor, Nurul Fitri; Mohd Sanusi, Zuraidah; Johari, Razana Juhaida; Saad Al-Dhubaibi, Ahmed Abdullah; Hudayati, Ataina; Abdul Razak, Nurshuhaida (Accounting Research Institute (ARI), 2022)
Many traditional approaches of accounting and auditing assessment have been transformed by the growth of audit technology. This study aimed to identify key factors driving auditors’ adoption of audit technology in a developing country, Malaysia, through the lens of the Technology to Performance Chain (TPC) framework. The results of this study are based on a survey conducted in Malaysia with audit firms of varying sizes and were analyzed using the Structural Equation Modelling-Partial Least Square (PLS) statistical tools. The direct and interaction effects of audit technology and situational support variables in improving auditor work performance, as well as the mediation effect of audit assessment on the connections, were investigated in this study. According to the findings, audit technology and situational support play a larger role in the efficiency and effectiveness of auditors' work. Additional analysis provides proof of audit assessment as well. This study makes several contributions to the literature including identifying new influential factors in the TPC framework. This framework has not been widely applied in auditing research and it looks beyond the individual perspective to that of the organization as a whole.